Educational leadership: skills of good public school principals in Panama - Esbrí Montoliú, Miguel Ángel; Durán González, Rosa Elena (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: To learn about the skills of the educational principal in Panama, for which we focus on schools with elementary school principals from 1st to 6th grade.Originality/Contribution: We provide a perspective on educational leadership in Panamanian schools based on the perceptions and experience of principals. Method: This project, of a mixed nature, mainly takes up the perceptions and experience of school principals on how they manage schools, the characteristics of principals, characteristics of schools, management course and activity, and institutional policy.Strategies / data collection: Quantitatively, the sample was taken from the general characterization of the educational centers registered in the educational system of the Republic of Panama, for the year 2020, provided by the Statistics Office of the Ministry of Education. Qualitatively, the "Survey on the Perception of Educational Leadership of Panama's Elementary School Principals" was designed, and direct and participant observation was carried out, as well as written and recorded oral surveys, where the principals expressed their opinions freely. Conclusions: The main characteristics that principals themselves should have to lead projects are self-organization, as managers, personal values and effective communication. Early monitoring by the Ministry of Education of teachers who demonstrate leadership skills is also important to motivate their training as possible successors in management.